Generation of a Conjoint Surface Plasmon by an Infrared Nano‐Antenna Array. Issue 2 (17th December 2020) - Allsop, Thomas; Mou, Chengbo; Neal, Ronald; Kundrát, Vojtěch; Wang, Changle; Kalli, Kyriacos; Webb, David; Liu, Xiaoping; Davey, Paul; Culverhouse, Philip; Diego Ania-Castañón, Juan
Abstract : Localized surface plasmons (LSP) excited by optical fields have many potential applications resulting from their ability in detecting ultra‐small, ambient refractive index change. Current methods using surface nano‐patterning by means of lithography have given rise to LSP of limited propagation and interaction lengths, meaning that practical applications remain challenging. This article describes a new all‐optical method of generating LSP by means of a carefully fabricated low‐dimensional nano‐structured material using a direct‐write photochemical lithography. It is shown that the resulting array of localized SPs combine or "Conjoin" to have an unprecedented large interaction length, via coupled evanescent fields, giving rise to superior spectral sensitivities; several orders of magnitude better than those quoted elsewhere and reaching 6 × 10 3  nm RIU −1 in the aqueous regime and 10 4  nm RIU −1 in the gaseous regime. Numerical modeling is performed that shows this design of plasmonic platform is capable of producing sensitivities of 10 5 –10 6  nm RIU −1 . It is believed the results achieved in this investigation show that a unique conjoint SP operational mode will significantly impact areas of interest, such as single molecular dynamics, drug delivery systems, etc. Abstract : A highly sensitive localized surface plasmon (LSP) sensing platform is reported. Using direct ultraviolet (UV) writing method, an array of nano‐antennae is formed on the top of an optical waveguide. In contrary to both conventional and LSP operational mode, a novel "conjoint surface plasmon" mechanism is identified.